The Positive Impact of Extensive Reading Through Wattpad for Students in Learning English as A Foreign Language (EFL) - Djamdjuri, Dewi Suriyani; Yuki, Librilianti Kurnia; Supriadi, Dedi; Retnowati, Nanik; Aulia, Sitinur Afifah; Khairunnisa, Arin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to determine students' experiences with comprehensive reading strategies using Wattpad. This study uses a qualitative descriptive research method. Data are collected using interviews, observation, documentation, and questionnaires. The analysis of this research uses a triangulation technique which consists of steps; data reduction, data display, and ultimately conclusion to analyze the data. The results of this study indicate that extensive reading through Wattpad can be used for pleasure, extensive reading through the Wattpad platform can reduce stress, extensive reading through Wattpad can increase motivation, and extensive reading through Wattpad can increase vocabulary. All of these activities can have a positive impact on students. Plus, Wattpad's platform is great for in-depth reading. Therefore, one of the best ways to learn English is to read extensively on the Wattpad platform. Teachers should realize that because Wattpad is a practical reading tool that can be accessed anywhere and at any time, all the stories students read must be age-appropriate.